Composite solid electrolyte membrane, preparation method thereof and solid lithium metal battery

By introducing high dielectric strength polysulfone organics into the composite solid electrolyte membrane, the problem of low electrochemical window of composite solid electrolytes is solved, the normal operation of the battery under the high voltage range and the rapid transmission of lithium ions is achieved, and the performance of the battery is improved.

CN119725714APending Publication Date: 2025-03-28SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411934666.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The electrochemical window of existing composite solid electrolytes is low, limiting the working ability of solid lithium metal batteries in high voltage range and the rapid transmission of lithium ions.

Method used

Polysulfone organic matter with high dielectric strength is introduced into the organic and inorganic composite membrane, and the composite solid electrolyte membrane is prepared by electrospinning technology, and impregnated and dried in the salt solution to significantly enhance the electrochemical window.

Benefits of technology

It significantly improves the electrochemical window of the composite solid electrolyte membrane, ensures that the battery works normally at a higher voltage range, promotes the rapid transmission of lithium ions, and improves the rate performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725714A_ABST
    Figure CN119725714A_ABST
Patent Text Reader

Abstract

The invention provides a composite solid electrolyte membrane, a preparation method thereof and a solid lithium metal battery. The preparation method comprises the following steps that an organic-inorganic composite membrane is provided, the organic-inorganic composite membrane comprises organic components and inorganic components, and the organic components comprise polysulfone organic matter; and soaking the organic-inorganic composite membrane in a salt solution, and drying to obtain the composite solid electrolyte membrane. According to the invention, the polysulfone organic matter with high dielectric strength is introduced into the organic-inorganic composite membrane, so that the electrochemical window of the composite solid electrolyte membrane is remarkably improved, and the normal work of the battery in a relatively high voltage range is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a composite solid electrolyte membrane and a preparation method thereof, and a solid lithium metal battery. Background Art

[0002] All-solid-state lithium metal batteries (ASSLBs) have an ultra-high theoretical energy density (>300Wh kg-1), which can essentially solve the energy density limitation and low safety problems of existing liquid metal batteries. They have been widely regarded as one of the most promising next-generation battery technologies. The core of solid-state metal batteries lies in solid electrolytes. At present, solid electrolytes are divided into three categories according to their chemical composition: inorganic solid ceramic electrolytes, organic solid polymer electrolytes and composite solid electrolytes (a combination of the first two types of materials). Polymer electrolytes are both flexible and low-cost, and are highly compatible with existing production lines, but they have problems such as poor mechanical strength, thermal stability, poor chemical stability, poor interface stability, and low voltage window. The composite solid electrolyte combines inorganic ceramic materials and organic polymers, has high ionic conductivity and good mechanical properties, and the electrochemical window of the organic component in the composite solid electrolyte plays a decisive role in the energy density of solid-state batteries.

[0003] Jiangneng Liang et al. published a paper entitled “Engineering the conductive carbon / PEOinterface to stabilize solid polymer electrolytes for all-solid-state highvoltage LiCoO 2In the paper entitled “Effects of Molecular Weight on the Electrochemical Properties of Poly (vinylidene difluoride)-Based Polymer Electrolytes”, Ying Liang et al. proposed that the electrochemical window of pure polyethylene oxide (PEO) is generally less than 3.8V. After positive electrode ALD coating, the electrochemical window of the obtained PEO-LLZTO organic-inorganic composite solid electrolyte is still less than 4.5V; in the paper entitled “Effects of Molecular Weight on the Electrochemical Properties of Poly (vinylidene difluoride)-Based Polymer Electrolytes”, the electrochemical windows of two pure PVDFs with different molecular weights were tested, and it was found that there was an obvious oxidation current at 4.22V; in the paper entitled “Composition regulation of polyacrylonitrile-based polymer electrolytes enabling dual-interfacially stable solid-state lithium batteries” published by Xiaoning Liu et al., it was found that the electrochemical window of pure PAN was about 4.5V. The low electrochemical windows of these organic substances seriously limit the development and application of high energy density solid electrolytes.

[0004] Therefore, how to effectively improve the electrochemical window of the composite solid electrolyte to ensure that the battery operates in a higher voltage range and that lithium ions are rapidly transported during operation is a technical problem that needs to be solved urgently. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a composite solid electrolyte membrane and a preparation method thereof and a solid lithium metal battery. The present invention introduces polysulfone organic matter with high dielectric strength into the organic-inorganic composite membrane, significantly improving the electrochemical window of the composite solid electrolyte membrane, ensuring that the battery can work normally in a higher voltage range and the rapid transmission of lithium ions during operation.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a composite solid electrolyte membrane, the preparation method comprising the following steps:

[0008] An organic-inorganic composite membrane is provided, wherein the organic-inorganic composite membrane comprises an organic component and an inorganic component, wherein the organic component comprises a polysulfone organic substance;

[0009] The organic-inorganic composite membrane is immersed in a salt solution and then dried to obtain the composite solid electrolyte membrane.

[0010] The present invention introduces polysulfone organic matter with high dielectric strength into the organic-inorganic composite membrane, significantly improving the electrochemical window of the composite solid electrolyte membrane, ensuring that the battery can work normally under a higher voltage range and the lithium ions can be quickly transmitted during the operation.

[0011] The preparation method provided by the invention has simple process, short preparation time, convenient operation and can realize large-scale production.

[0012] Preferably, the method for preparing the organic-inorganic composite film comprises the following steps:

[0013] The organic component and the inorganic component are added into the electrostatic spinning device respectively, and the two nozzles of the electrostatic spinning device simultaneously spin, and the organic-inorganic composite membrane is obtained after collection.

[0014] Preferably, the thickness of the organic-inorganic composite film is 5-35 μm, for example, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm or 35 μm.

[0015] Preferably, the mass ratio of the organic component to the inorganic component is (40-30):(60-70), wherein the selection range of the organic component "40-30" can be, for example, 30, 32, 34, 36, 38 or 40, and the selection range of the inorganic component "60-70" can be, for example, 60, 62, 64, 66, 68 or 70, etc.

[0016] In the present invention, the organic component and the inorganic component in a suitable mass ratio are helpful to form a three-dimensionally connected organic-inorganic interface, which is beneficial to the rapid transmission of lithium ions and improves the discharge rate of the battery.

[0017] Preferably, the polysulfone organic compound includes any one of bisphenol A polysulfone, polyphenylsulfone, polyethersulfone or aliphatic polysulfone, or a combination of at least two thereof.

[0018] Preferably, based on the mass of the organic component, the mass content of the polysulfone organic matter is 0.5-20%, for example, it can be 0.5%, 1%, 5%, 10%, 15% or 20%, etc., preferably 1-10%.

[0019] In the present invention, the polysulfone organic matter with an appropriate mass content can be more helpful in improving the working voltage of the organic-inorganic composite solid electrolyte. If the mass content of the polysulfone organic matter is too low, it is not conducive to high voltage operation, and if the mass content of the polysulfone organic matter is too high, it is not conducive to forming a three-dimensional interconnected structure with a high specific surface area.

[0020] Preferably, the organic component also includes a polymer material.

[0021] Preferably, the groups of the polymer material include any one of ether groups, carbonyl groups, ester groups, amine groups, fluorine groups, amide groups or nitrile groups, or a combination of at least two of them.

[0022] Preferably, the polymer material includes any one or a combination of at least two of polyacrylonitrile, polyvinyl pyrrolidone, polymethyl methacrylate, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene oxide, polypropylene oxide, polyethylene succinate, polyethylene sebacate, polyethylene glycol or polyethylene glycol diamine.

[0023] Preferably, the inorganic component includes any one of metal oxides, nitrides, fluorides, chlorides, carbides or lithium-based solid electrolytes, or a combination of at least two thereof.

[0024] Preferably, the metal oxide includes any one of zirconium oxide, titanium dioxide, aluminum oxide, silicon oxide, cerium oxide, manganese oxide, molybdenum oxide, tin oxide or zinc oxide, or a combination of at least two thereof.

[0025] Preferably, the nitride includes any one of boron nitride, aluminum nitride or titanium nitride, or a combination of at least two of them.

[0026] Preferably, the fluoride includes any one of zirconium fluoride, lithium fluoride, manganese fluoride or aluminum fluoride, or a combination of at least two thereof.

[0027] Preferably, the chloride includes any one of tin chloride, zinc chloride or lithium chloride, or a combination of at least two of them.

[0028] Preferably, the carbide includes any one of silicon carbide, boron carbide or zirconium carbide, or a combination of at least two of them.

[0029] Preferably, the lithium-based solid electrolyte includes any one of lithium lanthanum zirconium oxide, lithium lanthanum titanate or lithium aluminum titanium phosphate, or a combination of at least two thereof.

[0030] Preferably, the salt solution includes any one of a lithium salt solution, a sodium salt solution, a potassium salt solution, a magnesium salt solution, a zinc salt solution, an aluminum salt solution, an iron salt solution, a nickel salt solution, a cobalt salt solution, a manganese salt solution, an ammonium salt solution, a cadmium salt solution, a barium salt solution or a silver salt solution, or a combination of at least two thereof. For example, the lithium salt in the lithium salt solution can be lithium hexafluorophosphate, lithium thiocyanate, lithium perchlorate, lithium iodide, lithium bromide, lithium chloride, lithium nitrate, lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide LiTFSI, lithium difluorooxalate borate (LiDFOB) or lithium bis(oxalate borate) (LiBOB), and the sodium salt in the sodium salt solution can be sodium thiocyanate, sodium perchlorate, sodium iodide, sodium sulfide, sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethylsulfonyl)imide (NaTFSI), sodium difluorooxalate borate (NaDFOB) or sodium trifluoromethanesulfonate (NaCF 3 SO 3 ), etc. The potassium salt in the potassium salt solution may be potassium thiocyanate, potassium perchlorate, potassium bis(fluorosulfonyl)imide (KFSI), potassium bis(trifluoromethylsulfonyl)imide (KTFSI) or potassium hexafluorophosphate, etc. The magnesium salt in the magnesium salt solution may be magnesium thiocyanate, magnesium perchlorate, magnesium iodide, magnesium bromide, magnesium chloride, magnesium bis(trifluoromethylsulfonyl)imide (Mg(TFSI) 2 ) or magnesium trifluoromethanesulfonate (Mg(CF 3 SO 3 ) 2 ), etc. The zinc salt in the zinc salt solution can be zinc thiocyanate, zinc perchlorate, zinc iodide, zinc bromide, magnesium chloride, zinc trifluoromethanesulfonate (Zn(CF 3 SO 3 ) 2 ) or bis(trifluoromethylsulfonyl)imide)zinc (Zn(TFSI) 2 ), the aluminum salt in the aluminum salt solution may be aluminum thiocyanate, aluminum perchlorate, aluminum iodide, aluminum bromide, aluminum chloride or aluminum nitrate, etc., the iron salt in the iron salt solution may be ferric thiocyanate, ferric perchlorate, ferric iodide, ferric bromide, ferric chloride or ferric nitrate, etc., the nickel salt in the nickel salt solution may be nickel thiocyanate, nickel perchlorate, nickel iodide or nickel bromide, etc., the cobalt salt in the cobalt salt solution may be cobalt thiocyanate, cobalt perchlorate, cobalt iodide, cobalt bromide or cobalt nitrate, etc., the manganese salt in the manganese salt solution may be manganese thiocyanate, manganese perchlorate or manganese nitrate, etc., the ammonium salt in the ammonium salt solution may be ammonium chloride, ammonium sulfate or ammonium nitrate, etc., the cadmium salt in the cadmium salt solution may be cadmium chloride, cadmium nitrate or cadmium sulfate, etc., the barium salt in the barium salt solution may be barium chloride, barium nitrate or barium sulfate, etc., and the silver salt in the silver salt solution may be silver nitrate or silver sulfate, etc.

[0031] Preferably, the solvent of the salt solution includes any one or a combination of at least two of carbonate solvents, acetonitrile, N-methylpyrrolidone, water, methanol, ethanol, propanol, isopropanol, butanol, isobutanol, tert-butanol, ethylene glycol, propylene glycol, butanediol, diethylene glycol, triethylene glycol, tetraethylene glycol and at least triols.

[0032] Preferably, the concentration of the salt solution is 0.5-5 mol / L, for example, it can be 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L or 5 mol / L.

[0033] Preferably, the drying temperature is 60-100°C, for example, 60°C, 70°C, 80°C, 90°C or 100°C.

[0034] Preferably, the drying process includes baking.

[0035] Preferably, the preparation method comprises the following steps:

[0036] (1) A polysulfone organic matter, a polymer material and a solvent (the present invention does not limit the type of solvent, as long as it can dissolve the polysulfone organic matter and the polymer material, for example, it can be water, N-methylpyrrolidone, N,N-dimethylformamide, dimethyl sulfoxide, dimethylacetamide or an alcohol solvent, etc.) are mixed to obtain an organic component, and then the organic component and the inorganic component are added to an electrospinning device respectively. The two nozzles of the electrospinning device simultaneously spray and spin, and a film with a thickness of 50-200 μm (for example, 50 μm, 100 μm, 150 μm or 200 μm, etc.) is obtained after collection, and then rolled to obtain an organic-inorganic composite film with a thickness of 5-35 μm.

[0037] The specific parameters of the electrospinning method include: the distance between the two electrospinning nozzles and the receiving surface is 5-30 cm (for example, it can be 5 cm, 10 cm, 15 cm, 20 cm, 25 cm or 30 cm, etc.), the voltage is 5-50 kV (for example, it can be 5 kV, 10 kV, 20 kV, 30 kV, 40 kV or 50 kV, etc.), the flow rate is independently 0.1-100 μL / min (for example, it can be 0.1 μL / min, 1 μL / min, 10 μL / min), and the flow rate is 0.1-100 μL / min. L / min, 30μL / min, 50μL / min, 70μL / min or 90μL / min, etc.); the mass ratio of the organic component to the inorganic component is (40-30):(60-70) of the organic component and the inorganic component, the inorganic component includes any one of metal oxides, nitrides or lithium-based solid electrolytes or a combination of at least two of them, and the inorganic component also includes a solvent; based on the mass of the organic component, the mass content of the polysulfone organic matter is 0.5-20%.

[0038] (2) Immersing the organic-inorganic composite membrane in a salt solution with a concentration of 0.5-5 mol / L, and then drying it at 60-100° C. to obtain the composite solid electrolyte membrane.

[0039] The salt solution includes any one of lithium salt solution, sodium salt solution, potassium salt solution, magnesium salt solution, zinc salt solution, aluminum salt solution, iron salt solution, nickel salt solution, cobalt salt solution, manganese salt solution, ammonium salt solution, cadmium salt solution, barium salt solution or silver salt solution, or a combination of at least two thereof.

[0040] In a second aspect, the present invention provides a composite solid electrolyte membrane, which is prepared by the preparation method described in the first aspect.

[0041] In a third aspect, the present invention provides a solid-state lithium metal battery, wherein the solid-state lithium metal battery comprises the composite solid-state electrolyte membrane as described in the second aspect.

[0042] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] (1) The present invention introduces polysulfone organic matter with high dielectric strength into the organic-inorganic composite membrane, significantly improving the electrochemical window of the composite solid electrolyte membrane, ensuring that the battery can work normally in a higher voltage range and that lithium ions can be quickly transmitted during operation. The composite solid electrolyte membrane has low impedance and high voltage performance.

[0045] (2) The preparation method provided by the present invention has simple process, short preparation time, convenient operation, and can realize large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 Schematic diagram of the electrochemical window of the composite solid electrolyte membrane prepared in Example 1 of the present invention.

[0047] Figure 2 Impedance diagrams of the composite solid electrolyte membranes prepared in Example 1 and Comparative Example 1 of the present invention.

[0048] Figure 3 The impedance diagrams of the composite solid electrolyte membranes prepared in Example 4 and Comparative Example 2 of the present invention are shown respectively. DETAILED DESCRIPTION

[0049] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0050] Example 1

[0051] This embodiment provides a method for preparing a composite solid electrolyte membrane, the preparation method comprising the following steps:

[0052] (1) A polysulfone organic matter, a polymer material and N,N-dimethylformamide are mixed to obtain an organic component, and then the organic component and the inorganic component are added to an electrospinning device respectively. The two nozzles of the electrospinning device are simultaneously spun, and a film with a thickness of 120 μm is obtained after collection, and then rolled to obtain an organic-inorganic composite film with a thickness of 20 μm.

[0053] Among them, the polysulfone organic matter is bisphenol A type polysulfone, the polymer material is polyacrylonitrile, the inorganic component is boron nitride solution, and the solvent is N,N-dimethylformamide; the mass ratio of the organic component to the inorganic component is 35:65; the specific parameters of the electrostatic spinning method include: the distance between the two electrostatic spinning nozzles and the receiving surface is 20 cm, the voltage is 15 kV, the flow rate of the inorganic component is 50 μL / min, and the flow rate of the organic component is 10 μL / min; based on the mass of the organic component, the mass content of the polysulfone organic matter is 10%.

[0054] (2) The organic-inorganic composite membrane is immersed in a salt solution with a concentration of 1 mol / L, and then dried at 80° C. to obtain the composite solid electrolyte membrane.

[0055] The salt in the salt solution is lithium hexafluorophosphate, and the solvent for dissolving the salt includes ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) in a volume ratio of 1:1:1.

[0056] Figure 1 This is a schematic diagram of the electrochemical window of the composite solid electrolyte membrane prepared in this embodiment. It can be seen from the figure that the electrochemical window of the composite solid electrolyte membrane is greater than 5V.

[0057] Example 2

[0058] This embodiment provides a method for preparing a composite solid electrolyte membrane, the preparation method comprising the following steps:

[0059] (1) A polysulfone organic matter, a polymer material and N,N-dimethylformamide are mixed to obtain an organic component, and then the organic component and the inorganic component are added to an electrospinning device respectively. Two nozzles of the electrospinning device are simultaneously spun, and a film with a thickness of 50 μm is obtained after collection, and then rolled to obtain an organic-inorganic composite film with a thickness of 5 μm.

[0060] Among them, the polysulfone organic matter is polyphenylsulfone, the polymer material is polyethylene oxide, the inorganic component is zirconium oxide solution, and the solvent is N,N-dimethylformamide; the mass ratio of the organic component to the inorganic component is 30:70; the specific parameters of the electrostatic spinning method include: the distance between the two electrostatic spinning nozzles and the receiving surface is 20 cm, the voltage is 15 kV, the flow rate of the inorganic component is 50 μL / min, and the flow rate of the organic component is 10 μL / min; based on the mass of the organic component, the mass content of the polysulfone organic matter is 5%.

[0061] (2) The organic-inorganic composite membrane is immersed in a salt solution with a concentration of 0.5 mol / L, and then dried at 60° C. to obtain the composite solid electrolyte membrane.

[0062] Wherein, the salt in the salt solution is sodium perchlorate, and the solvent for dissolving the salt is propylene carbonate (PC).

[0063] Example 3

[0064] This embodiment provides a method for preparing a composite solid electrolyte membrane, the preparation method comprising the following steps:

[0065] (1) A polysulfone organic matter, a polymer material and N,N-dimethylformamide are mixed to obtain an organic component, and then the organic component and the inorganic component are added to an electrospinning device respectively. The two nozzles of the electrospinning device are simultaneously spun, and a film with a thickness of 200 μm is obtained after collection, and then rolled to obtain an organic-inorganic composite film with a thickness of 25 μm.

[0066] Among them, the polysulfone organic matter is polyethersulfone, the polymer material is polyethylene glycol diamine, the inorganic component is titanium dioxide solution, and the solvent is N,N-dimethylformamide; the mass ratio of the organic component to the inorganic component is 40:60; the specific parameters of the electrospinning method include: the distance between the two electrospinning nozzles and the receiving surface is 20 cm, the voltage is 15 kV, the flow rate of the inorganic component is 50 μL / min, and the flow rate of the organic component is 10 μL / min.

[0067] (2) The organic-inorganic composite membrane is immersed in a salt solution with a concentration of 2 mol / L, and then dried at 100° C. to obtain the composite solid electrolyte membrane.

[0068] The salt in the salt solution is lithium bis(difluorosulfonyl)imide, and the solvent for dissolving the salt is acetonitrile.

[0069] Example 4

[0070] The difference between this embodiment and embodiment 1 is that the polymer material is composed of polyethylene oxide and polyacrylonitrile in a mass ratio of 1:9, and the inorganic component is a zirconium oxide solution.

[0071] The rest of the preparation methods and parameters were the same as those in Example 1.

[0072] Example 5

[0073] The difference between this embodiment and embodiment 1 is that, based on the mass of the organic-inorganic composite membrane, the mass content of the polyphenylsulfone is 0.3%.

[0074] The rest of the preparation methods and parameters were the same as those in Example 1.

[0075] Example 6

[0076] The difference between this embodiment and embodiment 1 is that, based on the mass of the organic-inorganic composite membrane, the mass content of the polyphenylsulfone is 25%.

[0077] The rest of the preparation methods and parameters were the same as those in Example 1.

[0078] Comparative Example 1

[0079] The difference between this comparative example and Example 1 is that bisphenol A type polysulfone is not added in step (2).

[0080] The rest of the preparation methods and parameters were the same as those in Example 1.

[0081] Figure 2 The impedance diagrams of the composite solid electrolyte membranes prepared in Example 1 and this comparative example are shown. It can be seen from the diagram that the impedance of the composite solid electrolyte membrane provided by the present invention is significantly reduced.

[0082] Comparative Example 2

[0083] The difference between this comparative example and Example 4 is that bisphenol A type polysulfone is not added in step (2).

[0084] The rest of the preparation methods and parameters were the same as those in Example 4.

[0085] Figure 3 The impedance diagrams of the composite solid electrolyte membranes prepared in Example 4 and this comparative example are shown. It can be seen from the diagram that the impedance of the composite solid electrolyte membrane provided by the present invention is significantly reduced.

[0086] Comparative Example 3

[0087] The difference between this comparative example and Example 1 is that in step (2), bisphenol A type polysulfone is replaced by polyacrylonitrile.

[0088] The rest of the preparation methods and parameters were the same as those in Example 1.

[0089] Comparative Example 4

[0090] This comparative example provides a polysulfone nanofiber membrane for lithium batteries. The polysulfone nanofiber membrane is prepared by dissolving bisphenol A polysulfone in N,N-dimethylformamide, stirring to obtain a polysulfone solution, and then electrospinning the polysulfone solution.

[0091] Performance Testing

[0092] The membranes provided in the above examples and comparative examples were tested for ionic conductivity, impedance performance and electrochemical window.

[0093] Among them, the AC impedance method was used to test the ionic conductivity and impedance, and the linear scanning voltammetry method was used to test the electrochemical window.

[0094] The test results are shown in Table 1.

[0095] Table 1

[0096]

[0097]

[0098] analyze:

[0099] As can be seen from the table, the present invention is based on an organic-inorganic composite membrane and introduces polysulfone organic matter with high dielectric strength, which significantly improves the electrochemical window of the composite solid electrolyte membrane and ensures that the battery can work normally in a higher voltage range.

[0100] It can be seen from Example 1 and Examples 5-6 that if the mass content of bisphenol A type polysulfone is too low, it is not conducive to the high voltage operation of the composite solid electrolyte membrane, and the electrochemical window is <5V. If the mass content of bisphenol A type polysulfone is too high, it is not conducive to the formation of a three-dimensional interconnected structure with a high specific surface area, resulting in low conductivity and increased impedance, which is not conducive to the battery rate performance.

[0101] From the comparison between Example 1 and Comparative Example 1, or between Example 4 and Comparative Example 2, it can be seen that if bisphenol A type polysulfone is not added, the electrochemical window will be reduced.

[0102] It can be seen from Example 1 and Comparative Example 3 that if bisphenol A type polysulfone is replaced with polyacrylonitrile, the impedance increases and a high voltage cannot be achieved.

[0103] It can be seen from Example 1 and Comparative Example 4 that if the polysulfone nanofiber membrane provided by the prior art is used, the impedance is large and it is difficult to ensure the conductivity of the solid electrolyte.

[0104] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a composite solid electrolyte membrane, characterized in that: The preparation method comprises the following steps: An organic-inorganic composite membrane is provided, wherein the organic-inorganic composite membrane comprises an organic component and an inorganic component, wherein the organic component comprises a polysulfone organic substance; The organic-inorganic composite membrane is immersed in a salt solution and then dried to obtain the composite solid electrolyte membrane.

2. The preparation method according to claim 1, characterized in that: The method for preparing the organic-inorganic composite film comprises the following steps: Adding organic components and inorganic components to an electrospinning device respectively, and spinning simultaneously with two nozzles of the electrospinning device, and collecting to obtain the organic-inorganic composite film; Preferably, the thickness of the organic-inorganic composite film is 5-35 μm.

3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the organic component to the inorganic component is (40-30):(60-70).

4. The preparation method according to any one of claims 1 to 3, characterized in that The polysulfone organic compound includes any one of bisphenol A polysulfone, polyphenylsulfone, polyethersulfone or aliphatic polysulfone, or a combination of at least two thereof; Preferably, based on the mass of the organic component, the mass content of the polysulfone organic matter is 0.5-20%, preferably 1-10%.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The organic component also includes polymer materials; Preferably, the polymer material includes any one or a combination of at least two of polyacrylonitrile, polyvinyl pyrrolidone, polymethyl methacrylate, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene oxide, polypropylene oxide, polyethylene succinate, polyethylene sebacate, polyethylene glycol or polyethylene glycol diamine; Preferably, the inorganic component includes any one or a combination of at least two of metal oxides, nitrides, fluorides, chlorides, carbides or lithium-based solid electrolytes; Preferably, the metal oxide includes any one of zirconium oxide, titanium dioxide, aluminum oxide, silicon oxide, cerium oxide, manganese oxide, molybdenum oxide, tin oxide or zinc oxide, or a combination of at least two thereof; Preferably, the nitride comprises boron nitride; Preferably, the lithium-based solid electrolyte includes any one of lithium lanthanum zirconium oxide, lithium lanthanum titanate or lithium aluminum titanium phosphate, or a combination of at least two thereof.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The salt solution includes any one of a lithium salt solution, a sodium salt solution, a potassium salt solution, a magnesium salt solution, a zinc salt solution, an aluminum salt solution, an iron salt solution, a nickel salt solution, a cobalt salt solution, a manganese salt solution, an ammonium salt solution, a cadmium salt solution, a barium salt solution or a silver salt solution, or a combination of at least two thereof; Preferably, the solvent of the salt solution comprises any one or a combination of at least two of carbonate solvents, acetonitrile, N-methylpyrrolidone, water, methanol, ethanol, propanol, isopropanol, butanol, isobutanol, tert-butanol, ethylene glycol, propylene glycol, butanediol, diethylene glycol, triethylene glycol, tetraethylene glycol and at least triols; Preferably, the concentration of the salt solution is 0.5-5 mol / L.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The drying temperature is 60-100°C; Preferably, the drying process includes baking.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) mixing a polysulfone organic matter, a polymer material and a solvent to obtain an organic component, and then adding the organic component and the inorganic component to an electrospinning device respectively, and the two nozzles of the electrospinning device simultaneously spray spinning, and after collecting, a film with a thickness of 50-200 μm is obtained, and then rolling is performed to obtain an organic-inorganic composite film with a thickness of 5-35 μm; The specific parameters of the electrospinning method include: the distance between the two electrospinning nozzles and the receiving surface is 5-30 cm, the voltage is 5-50 kV, and the flow rate is independently 0.1-100 μL / min; the mass ratio of the organic component to the inorganic component is (40-30): (60-70), the inorganic component includes any one of metal oxides, nitrides or lithium-based solid electrolytes or a combination of at least two, and the inorganic component also includes a solvent; based on the mass of the organic component, the mass content of the polysulfone organic matter is 0.5-20%; (2) immersing the organic-inorganic composite membrane in a salt solution with a concentration of 0.5-5 mol / L, and then drying it at 60-100° C. to obtain the composite solid electrolyte membrane; The salt solution includes any one of lithium salt solution, sodium salt solution, potassium salt solution, magnesium salt solution, zinc salt solution, aluminum salt solution, iron salt solution, nickel salt solution, cobalt salt solution, manganese salt solution, ammonium salt solution, cadmium salt solution, barium salt solution or silver salt solution, or a combination of at least two thereof.

9. A composite solid electrolyte membrane, characterized in that: The composite solid electrolyte membrane is prepared by the preparation method according to any one of claims 1 to 8.

10. A solid-state lithium metal battery, characterized in that: The solid-state lithium metal battery comprises the composite solid-state electrolyte membrane as claimed in claim 9.

Citation Information

Cited By

  • Method for preparing semi-solid energy storage composite electrolyte for gas turbine black start and electrolyte

    CN122696765A

  • Method for preparing semi-solid energy storage composite electrolyte for gas turbine black start and electrolyte

    CN122696765B